Challenges and success factors of transnational higher education: a systematic review - Tran, Nguyen Hai Ngan (2022)
This paper provides an analysis of the literature on transnational education to identify the key challenges and success factors for the sustainable operation of transnational higher education (TNE) programmes as perceived by key stakeholders. Probing the stakeholders' perspectives and applying a systematic approach, this study analyses 227 English-written articles retrieved from the Web of Science database published from 2000 to 2021. Key challenges identified include difficulties in managing the TNE programmes, ensuring quality assurance, adapting the curricula to the local contexts, accommodating offshore students' learning styles, creating studying environments for TNE students equivalent to those in the home institutions, ensuring preparedness of the academic staff, and facilitating the knowledge transfer in the host countries. The analysis also highlights six factors for the sustainable development of TNE programmes, including the effectiveness of the operations, the internationalization of the curricula, the transnational experience of the students, the development of the transnational staff, the existence of a proper regulatory framework in the host countries, and the development of a global systematic data collection for quality assurance. In addition, the evidence collected suggests that while the transition from domestic into a foreign programme can be rewarding, it demands appropriate planning and implementation.